Studi Carbon Footprint dari Kegiatan Pabrik Minyak Sawit PT. Johan Sentosa di Bangkinang, Riau - Lestari, Wanda; Sasmita, Aryo; Asmura, Jecky (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Climate change is one of the effects of global warming caused by the greenhouse effect by increasing concentration of greenhouse gases. In response to global warming Indonesia goverment is committed to reducing greenhouse gas emissions 26% by its own effort and 41% if it receives international assistance in 2020. One of the industrial sectors that contributes to greenhouse gas emissions in Indonesia is the Palm Oil Mill (POM) . To find out the total of CO2 emissions produced uses method by Intergovermental Panel on Cilmate Change (IPCC). Total emissions from POM PT. Johan Sentosa is 115.015,18 CO2 eq/year.Keywords: Palm Oil Mill (POM), IPCC, CO2